Effects of Alternative Milk on Streptococcus Mutans Biofilm Formation and Enamel Demineralization in Human Primary Teeth - Srivoha, Naruemon; Asvanund, Yuwadee; Mitrakul, Kemthong; Srisatjaluk, Ratchapin (European Journal of General Dentistry, 2025)
Objectives This study was conducted to investigate the effects of alternative milk on Streptococcus mutans biofilm formation and their ability to demineralize enamel in primary teeth.Materials and Methods First, to evaluate the effects of cow milk, lactose-free cow milk, goat milk, unsweetened pistachio milk, and sweetened pistachio milk on S. mutans biofilm formation, biofilm assay was conducted. The optical density (OD) was measured to determine S. mutans biofilm. Second, to assess the enamel demineralization, enamel slabs were prepared from 50 primary incisor teeth and divided into three test groups, along with positive and negative control groups. Enamel slabs were immersed in each type of milk three times a day for 5 days. The percentage of surface hardness loss (%SHL) for enamel demineralization was measured. One enamel slab was randomly selected from each group to visualize the enamel opacity in demineralization area by using a light microscope. Another slab was randomly selected from each group to stain with fluorescence dye and to observe the biofilm structure by using a confocal microscope.Results The OD ± SD (standard deviation) measurements for S. mutans biofilm formation in cow milk, lactose-free cow milk, goat milk, unsweetened pistachio milk, and sweetened pistachio milk were 0.082 (± 0.002), 0.086 (± 0.004), 0.083 (± 0.007), 0.0952 (± 0.010), and 0.342 (± 0.072), respectively. The sweetened pistachio milk exhibited significantly more biofilm formation than the other milk (p < 0.05). Since there was no significant difference in biofilm formation among cow milk, lactose-free cow milk, goat milk, and unsweetened pistachio milk, we tested the enamel demineralization only with cow milk, unsweetened pistachio milk, and sweetened pistachio milk. The %SHL (± SD) for cow milk, unsweetened pistachio milk, and sweetened pistachio milk were 20.01 (± 2.618), 22.088 (± 3.4), and 35.49 (± 2.069), respectively. The %SHL on the enamel in sweetened pistachio milk was higher (p < 0.001) than other tested milk. White spot lesion was directly visualized on slabs in sweetened pistachio milk under light microscope. Biofilm formed in sweetened pistachio milk demonstrated a mushroom-like structure, whereas cow milk and unsweetened pistachio milk had a flat biofilm structure.Conclusion Sweetened pistachio milk increases the risk for primary incisor teeth caries formation greater than cow milk and unsweetened pistachio milk regarding S. mutans biofilm formation was higher in quantity and ability to demineralization in primary teeth.
Keywords: alternative milk; biofilm; enamel demineralization; streptococcus mutans